Factors for containing failure and abandonment of public sector construction projects in Nigeria - Amade, B.; Ubani, E.C.; Amaeshi, U.F.; Okorocha, K.A. (Penerbit UKM, 2015)
The objective of this study was to identify possible factors that would minimize or contain failure and abandonment of public sector construction projects, evaluate the identified factors in their order of importance. Data on the study variables were collected through structured questionnaire from construction firms located in Imo, Abia and Rivers States of Nigeria with wealth of experience in failed and abandoned public sector construction projects. Respondents were approached personally to collect the data. A total of three hundred (300) questionnaires were distributed while two hundred and fifty three (253) were retrieved and used for analysis. Various statistical tools such as descriptive statistics, cronbach's alpha test, as well as relative importance index with the aid of SPSS and Microsoft Excel were applied for data analysis and inference. The results of the study revealed that nine factors were critical in containing failure and abandonment of public sector construction projects in Nigeria. The factors include; Detailed and Comprehensive Design by the Contractors, Effective Monitoring, Understanding of Project’s Mission, Technical Knowhow of the Project Manager, Support from Top Management, Political Risks, Effective Procurement Process, Provision of Adequate Finance by the Client, and Effective Communication and Information Management by Design Team.